(untitled) (CIPEEX, 2024)
The aim of this research project was to evaluate the dental discoloration caused by filling pastes used in pediatric dentistry. Blocks of bovine lower incisor crowns were prepared, leaving a 2 mm thick enamel and dentin remnant. The blocks were randomly assigned into 2 groups, according to the presence or absence of dentin hybridization. After hybridization, the blocks were further subdivided into 5 experimental groups based on the type of endodontic cement: 1) Guedes Pinto Paste; 2) Zinc oxide-eugenol paste; 3) Calcium hydroxide paste, prepared with calcium hydroxide and propylene glycol; 4) Paste containing Chloramphenicol + tetracycline chloride + zinc oxide-eugenol; 5) Vitapex®. Color determination was performed using a digital spectrophotometer, and measurements were obtained at 7, 30, and 60 days after the material placement. Data related to discoloration were tabulated and tested for normality using the Shapiro-Wilk test. ANOVA and Tukey tests were used for analysis. Both the filling paste and evaluation period showed statistical differences in color alteration (p < 0.05). Endodontic pastes induce staining of the dental structure.